Systematic pad dry cure technique for augmenting the flame resistance functionality of jute fabric - Md. Reazuddin Repon; Halima Tus Sadia; Tarikul Islam; Mohammed M. Rahman; Md. Rezaul Karim (Cleaner Engineering and Technology, 2022)
Applying flame retardant finish on jute makes flame protective jute products that can be another diversified use of it. The target of this experiment is to observe the flame retardancy improvement of the fabric properties after finishing treatment with various flame retardant chemicals. The untreated (raw) and H2O2 bleached jute fabrics having plain weave were used in this experiment. Borax, diammonium phosphate (DAP) and thiourea were used as flame retardant chemicals. The combinations of these chemicals were applied to the fabrics by the pad-dry-cure method with various concentrations. Vertical flammability, breaking load percentage, and weight gain percentage were performed on all samples to observe the change in fabric properties. Significant improvement was found for all chemical combinations compared to untreated fabrics. Here, the flame spread time and weight gain percentage increase, but the breaking load percentage decreases for every combination. Among all combinations, the borax and DAP combination especially at 6% concentration shows the 305% improvement of flame spread time for raw jute and 276% for bleached jute fabric. In contrast, the borax and thiourea combination showed the progress of weight gain percentage. Besides, better wash durability was reported for all samples after five washing cycles. These flame-retardant jute fabrics have prospective industrial applications as brattice cloth in mines and many other potential fields of applications such as flame-retardant kitchen aprons, furnishings for a public hall, theater and hospitals.